Synthesis of Sulphonated Carbon Catalyst from Coconut Shell and its Application in Esterification of Free Fatty Acid in Used Cooking Oil - Ulfah, Maria; Pasymi, Pasymi; Burmawi, Burmawi; Amir, Amelia (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Coconut shells are a prevalent agricultural waste product in Indonesia. Currently, there is a trend toward developing heterogeneous catalysts for the esterification reaction of vegetable oils to produce biodiesel. These catalysts are made from biomass carbon. This research aims to investigate the effectiveness of using carbon precursors derived from coconut shells to create a heterogeneous acid catalyst for the esterification of waste cooking oil (WCO). Another objective is to identify the optimal esterification reaction conditions catalyzed by the developed sulfonated carbon catalyst, which exhibits the highest performance in converting free fatty acids (FFA). The coconut shells were carbonized using conventional methods and functionalized with concentrated sulfuric acid through dry impregnation. This process was conducted under various sulfonation conditions. The varied preparation parameters included the carbon-acid ratio (1:7.1, 1:10, 1:12.8, and 1:15.7% w/v), contact time (1 to 4 days), and calcination temperature (270C, 340C, and 450C). The charcoal and catalyst developed in this research were characterized through composition analysis using X-ray fluorescence (XRF) and crystal phase analysis using X-ray diffraction (XRD). The best catalyst preparation conditions were determined to be a carbon-acid ratio of 1:15.7% (w/v), a contact time of 3 days, and a calcination temperature of 340C. The optimal esterification reaction conditions were achieved using a mole ratio of methanol to WCO of 12:1, with a catalyst amount of 1.6%, for a duration of 1 hour at a temperature of 60C. This reaction resulted in a conversion rate of 84.6%.